Pergeseran Aturan Netralitas Aparatur Sipil Negara dalam Pemilihan Umum - Bagus Sarnawa (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
The State Civil Apparatus (ASN) is the executor of government and development tasks. Therefore the ASN must be neutral. Based on Law Number 5 of 2014, the neutrality of the ASN is free from the influence and intervention of all political parties and groups. To maintain and guarantee the neutrality the integrity, cohesiveness, and unity of the State Civil Apparatus from the influence of political parties and to focus all attention, mind and energy on the tasks charged, the ASN is prohibited from becoming a member and/or administrator of political parties. In the past, the neutrality of the ASN began in the Old Order, when the issuance of Presidential Regulation Number 2 of 1959 concerning the Prohibition of Civil Servants and Public Officials in Political Parties. Furthermore, this Presidential Regulation was followed up and expanded with a Circular Letter of the President of the Republic of Indonesia Number 2 of 1959 concerning Prohibition of Membership of Political Parties for State Officials that Carry Out State Obligations Outside of Positions which they hold. Furthermore, in the New Order period, Law Number 8 of 1974 concerning the Principles of Staffing, while during the Reform Order was issued, among others, Law Number 43 of 1999, Civil servants must be neutral from the influence of all groups and parties and not discriminatory in providing services to the public. And the Reform Order was issued Law Number 5 of 2014 and other regulations related to the neutrality of the ASN